A mixture of canonical vine copula-GARCH approach for modeling dependence of European electricity markets - Jiechen Tang (2018)
© 2014 by the Mathematical Association of Thailand. All rights reserved. This paper employed a mixed Canonical Vine Copula-GARCH approach for modeling the dependence structures of European electricity markets. The electricity spot prices are taken from French, German, Spanish, Dutch, and British markets. The empirical result shows that pairwise positive dependence between markets is represented in Tree 1, in which there is positive spillover effect between the French and the other four markets. Moreover, the French, German, and Dutch markets have strong symmetric tail dependence, which suggests one market (one of the French, German, or Dutch markets) experiencing spikes or drops, conditional on the event that the other two markets are also experiencing spikes or drops. Additionally, we also found that when adding the condition under one or more markets, the relationships of some pairs still had dependence, while some other pairs became independent.